The Effects of an Ethics Education Program on Artificial Intelligence among Middle School Students: Analysis of Perception and Attitude Changes - Choi, Jung In; Yang, Eunja; Goo, Eun Hee (Applied Sciences (Switzerland), 2024)
Artificial intelligence (AI) technology has brought convenience to human lives, but its pervasive impact extends beyond individuals, affecting society as a whole. Consequently, the necessity for an AI ethics education program has become increasingly apparent. This study aims to investigate the influence of an experimental research study that developed and implemented an AI ethics education program for learners’ ethical awareness and attitude towards AI. The research methodology involved validating a model of the AI ethics education program by applying it to a group of 10 domain experts. Additionally, pre-test and post-test designs were employed with 17 middle school students as the experimental group. The same assessment was administered before and after the implementation of the AI ethics education program, and the data were analyzed using paired-sample t-tests. The findings of this study are as follows: Firstly, an AI ethics education program model was developed, incorporating key competencies such as AI literacy, critical thinking skills in AI, and AI problem-solving skills, all within the context of AI ethics. The implementation of this model was effective in the educational setting. Secondly, significant improvements were observed in the ethical awareness of middle school students across all domains after participating in the program. Thirdly, the attitudes of middle school students towards AI exhibited significant enhancements across all domains. These findings contribute to the broader field of AI ethics education by highlighting the importance of ethical awareness in AI and fostering favorable attitudes towards AI. The implications of this study are significant for the field of AI education.
Keywords: artificial intelligence; attitudes toward artificial intelligence; ethical awareness; ethics education program; middle school students